2003
DOI: 10.1046/j.1523-1755.2003.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kt/V on survival and clinical outcome in CAPD patients in a randomized prospective study

Abstract: Patients with total Kt/V maintained below 1.7 had significantly more clinical problems and severe anemia but there was no difference in outcome demonstrated for patients with Kt/V maintained above 2.0 and between 1.7 and 2.0. We recommended that the minimal target of total Kt/V should be above 1.7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
5
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(176 citation statements)
references
References 21 publications
(18 reference statements)
7
156
5
7
Order By: Relevance
“…On the one hand, the greater membrane solute transport rate will enhance small solute clearance (although not necessarily during more prolonged dwells [45]); on the other hand, it may enhance protein losses, leading to malnutrition and diminished fluid removal. Recent randomized trials and observational studies now support the notion that peritoneal solute clearance does not significantly influence patient outcome within usual PD dosing regimens (22,46,47), whereas clinical volume status may (15,46,48,49). Our meta-analysis is consistent with these observations.…”
Section: Discussionsupporting
confidence: 81%
“…On the one hand, the greater membrane solute transport rate will enhance small solute clearance (although not necessarily during more prolonged dwells [45]); on the other hand, it may enhance protein losses, leading to malnutrition and diminished fluid removal. Recent randomized trials and observational studies now support the notion that peritoneal solute clearance does not significantly influence patient outcome within usual PD dosing regimens (22,46,47), whereas clinical volume status may (15,46,48,49). Our meta-analysis is consistent with these observations.…”
Section: Discussionsupporting
confidence: 81%
“…Patient survival on PD in The Netherlands has somewhat improved over the past 10 years (3). The rate we found corresponds with that found in another national study (21), is higher than rates reported from some American studies (4,7), and is somewhat lower than in Asian studies (22,23).…”
contrasting
confidence: 51%
“…Previously, adequacy targets for peritoneal dialysis (PD) patients were founded on both urea and creatinine kinetics based on the original interpretation of the results from the CANUSA trial (1). In recent years, minimum adequacy targets for PD patients have been altered based upon results from the ADEMEX and Hong Kong trials (2,3). The ADEMEX trial found no difference in survival of patients who received an average urea Kt/V of 1.80 or 2.27, and the Hong Kong trial similarly found no improvement in survival if patients received urea Kt/V of greater than 1.5 -1.7.…”
mentioning
confidence: 99%